Diagnostic significance of calf circumference in sarcopenia of healthy korean adult males - Kim, Gwon-Min; Song, Seunghwan; Park, Jong-Hwan; Tak, Young Jin; Wang, Il Jae; Huh, Up; Cho, Jeong Su (Frontiers in Physiology, 2022)
This study aimed to determine the relationship between sarcopenia and physical function, and the best method of diagnosing sarcopenia in healthy adults. Early prevention of sarcopenia is important; however, no studies have been conducted in healthy and relatively young adults. In addition, it remains unclear whether calf circumference is associated with sarcopenia-defined variables. A total of 85 healthy male participants were enrolled, and the mean (SD) age of the participants was 59.76 (8.12) years. Abdominal computed tomography (CT) was performed to measure muscle areas. All subjects were divided into sarcopenia and non-sarcopenia groups based on skeletal muscle mass index using CT. Sarcopenia showed a tendency to be related to lower grip strength, five times sit-to-stand and timed up and go tests for physical function. This result shows that overweight and obesity in the sarcopenia group had fully adjusted odds ratios of 0.026 (95% CI: 0.002–0.317) and 0.008 (95% CI: 0.001–0.096), respectively. Calf circumference was higher specificity (71.43 and 64.86) better than bioelectrical impedance analysis-based skeletal mass index and had a similar sensitivity (72.09 and 82.35). In conclusion, calf circumference suggests the need to consider its use as a tool for assessing muscle mass in the diagnosis of sarcopenia.